A new model to simulate the creep behavior of graphene/epoxy nanocomposites. (May 2019) - Shokrieh, Z.; Shokrieh, M.M.
Abstract: In the present research, the creep behavior of graphene/epoxy nanocomposites with a random distribution of nanographene was simulated. Recently, the present authors modified two micromechanical models to simulate the creep modulus and the total strain of graphene/epoxy nanocomposites. The modified micromechanical models showed good accuracy in the low graphene content (<0.25 wt%), but by increasing the graphene content (>0.25 wt%) the error of the modified micromechanical models increased. In this paper, the combined finite element-micromechanics (FE-M) model previously developed by the present authors for the prediction of the elastic properties of nanocomposites was modified and extended to predict the time-dependent creep properties of nanocomposites. The present model is called the extended combined finite element-micromechanics (X-FE-M) model . To this end, a representative volume element of nanocomposites, containing an aligned graphene sheet surrounded by the polymer, was simulated using the finite element method. An available micromechanics relation for calculation of the stiffness of graphene/epoxy nanocomposites with aligned graphene was extended to consider the random distribution of graphene sheets in the polymer. Finally, the total strain of nanocomposites as a function of time was obtained using the creep modulus of nanocomposites. The results show that the present model simulates the creep behavior of high graphene content (>0.25 wt%) nanocomposites with higher accuracy in comparison with the modified micromechanical models. Highlights: The combined FE-M model previously developed by the present authors for prediction of the elastic properties of nanocomposites was modified and extended to predict the time-dependent creep properties of nanocomposites. An available micromechanical relation for calculation of the stiffness of graphene/epoxy nanocomposites with aligned graphene was extended to consider the random distribution of graphene sheets in the polymer. A representative volume element of nanocomposites, containing an aligned graphene sheet surrounded by the polymer, was simulated using the finite element method. The total strain of nanocomposites as a function of time was obtained using the creep modulus of nanocomposites. The obtained results were found to be in a very good agreement with the available experimental results, confirming the validity of the proposed method.